Answer:
The answer is x=−1247
Step-by-step explanation:
Let's solve your equation step-by-step.
1+39(12−44)=x
Step 1: Simplify both sides of the equation.
1+39(12−44)=x
1+−1248=x
(1+−1248)=x(Combine Like Terms)
−1247=x
−1247=x
Step 2: Flip the equation.
Answer: x=−1247
Answer:
A. -12h² - 22h + 14
Step-by-step explanation:
(-4h +2)(3h +7) = -4h(3h +7) +2(3h +7) . . . . . . . (a +b)c = ac +bc
= (-4h)(3h) + (-4h)(7) + (2)(3h) + (2)(7) . . . . . . . a(b +c) = ab +ac . . . (twice)
= -12h² -28h +6h +14
= -12h² -22h +14 . . . . . . . . collect terms
X=3 pretty sure
Hope this helps!!